'I was flying blind a wee bit': Professionals' perspectives on challenges facing communication assistance in the New Zealand youth justice system. (April 2020) - Howard, Kelly; McCann, Clare; Dudley, Margaret
Communication assistance is a form of specialist support for witnesses and defendants in justice settings who have been identified as having communication difficulties. This relatively new role in New Zealand is modelled on the role of the intermediary in England and Wales. This research provides a qualitative analysis of professionals' perspectives (n = 28 participants) on the challenges of communication assistance for young people facing criminal charges in the New Zealand youth justice system. The findings of this study do not question whether or not communication assistance should exist, but rather how it might best function in practice. The overall implications are that more education and guidance for youth justice professionals is needed.